2020
DOI: 10.1186/s12864-020-6548-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of MAPKKK genes and their responses to phytoplasma infection in Chinese jujube (Ziziphus jujuba Mill.)

Abstract: Background: Mitogen-activated protein kinase (MAPK) cascades play vital roles in signal transduction in response to a wide range of biotic and abiotic stresses. In a previous study, we identified ten ZjMAPKs and five ZjMAPKKs in the Chinese jujube genome. We found that some members of ZjMAPKs and ZjMAPKKs may play key roles in the plant's response to phytoplasma infection. However, how these ZjMAPKKs are modulated by ZjMAPKKKs during the response process has not been elucidated. Little information is available… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…With the identification of MAPK cascade gene families in different plant species, we found that the gene number of MAPK family, MAPKK family and MAPKKK family differed among species. There were 20 MAPK genes in A. thaliana (Colcombet & Hirt, 2008; Ichimura et al, 2002; Jonak et al, 2002), 19 in P. trichocarpa , 14 in V. vinifera (Cakir & Kilickaya, 2015; Wang et al, 2014a), 14 in C. sativus (Wang et al, 2015), 13 in E. ulmoides , 12 in J. curcas (Wang et al, 2018), and 10 in Z. jujuba (Liu et al, 2017; Liu et al, 2020). The MAPKK genes were 10, 9, 5, 6, 5, 5, 5, 5 and the MAPKKK genes were 80, 104, 62, 59, 57, 65, 56, respectively in the above‐mentioned species.…”
Section: Discussionmentioning
confidence: 99%
“…With the identification of MAPK cascade gene families in different plant species, we found that the gene number of MAPK family, MAPKK family and MAPKKK family differed among species. There were 20 MAPK genes in A. thaliana (Colcombet & Hirt, 2008; Ichimura et al, 2002; Jonak et al, 2002), 19 in P. trichocarpa , 14 in V. vinifera (Cakir & Kilickaya, 2015; Wang et al, 2014a), 14 in C. sativus (Wang et al, 2015), 13 in E. ulmoides , 12 in J. curcas (Wang et al, 2018), and 10 in Z. jujuba (Liu et al, 2017; Liu et al, 2020). The MAPKK genes were 10, 9, 5, 6, 5, 5, 5, 5 and the MAPKKK genes were 80, 104, 62, 59, 57, 65, 56, respectively in the above‐mentioned species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ZjMKK5 was specifically expressed in flower buds, whereas ZjMKK2 was largely expressed in fruits. A subsequent study identified a total of 56 ZjMAPKKKs, but unfortunately, their expression profile in fruit development was not reported [44]. In grapevines, Wang et al (2014) [45] identified 45 VviMAPKKK genes in the grapevine genome.…”
Section: Recent Studies On Patterns Of Gene Expression Of Maps Kinase...mentioning
confidence: 99%
“…The scions grafted on healthy rootstocks were analyzed as a negative control and named "PZ_H" and "T13_H, " H meaning healthy. All experimental trees were cultivated under natural environmental conditions (Liu et al, 2020b). After grafting to the first time of sample collection, the scions began sprouting, spreading leaves, and grew up.…”
Section: Plant Materials and Phytoplasma Quantificationmentioning
confidence: 99%